Ergonomic Analysis of a Modified Dishwashing Facility in a Medium Scale Restaurant - Achmad Yahya Teguh Panuju; Sandi Kurniawan; Arinal Hamni (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2025)
Dishwashing is a crucial stage in the production process of restaurants, where ergonomic aspects for the operators play an important role in determining overall productivity. To support the performance improvement of small and medium enterprises (SMEs), this study conducted an experimental analysis to evaluate the ergonomic level of dishwashing activities in a restaurant located in Bandar Lampung. Prior to the assessment, modifications had been made to the design of the dishwashing facility. The evaluation was carried out using the Ovako Work Posture Analysis System (OWAS), energy consumption analysis, the Nordic Body Map (NBM) questionnaire, and an investigation of the relationship between ergonomic levels and operator productivity. The results revealed that the modified design significantly improved the ergonomic quality of the facility and led to a measurable increase in operator productivity. These findings demonstrate that workplace design improvements in SMEs can effectively enhance both ergonomics and business performance.